Parenting of people with visual disabilities as an interdisciplinary context of contemporary special education - Wałachowska, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The aim of the article is to present the issues of parenting of people with visual disabilities as a factor that dynamizes development, against the background of selected interdisciplinary contexts (psychological, functional, pedagogical). The sphere of personality-emotional development was presented through a psychological context. The functional sphere is represented by the functional context, and the development in the cognitive area has been based on the pedagogical context. The study was summarized indicating areas requiring scientific penetration in the social context of the functioning of the parental practice of the blind and visually impaired. The text was based on the method of descriptive and critical literature analysis.